Factors affecting the health of nursing teachers at the University of Guayaquil - Ramírez Pérez, Taycia; Rebolledo Malpica, Dinora; García Martínez, María Araceli; Quijije Díaz, Rina Vanessa (Revista Universidad de Guayaquil, 2023)
Health encompasses subjective aspects, such as physical, mental and social well-being, determined by the human being’s capacity to function and adapt, which enable a good experiential relationship. In this sense, a study was carried out with the objective of determining the risk factors that affect the physical and mental health of nursing teachers. An Action-Research-Participation methodology was used, which allowed a diagnosis of the needs and problems in the daily spaces of their activity as participants. The problems were listed and defined according to magnitude, transcendence, seriousness, impact and finally prioritized, emphasizing causes, effects, and consequences. Subsequently, an action plan was drawn up within an FCI project. The population was confirmed by 10 teachers of nursing of the university of Guayaquil, who have been working for more than 2 years in the career and lived the experience of assuming the telework in pandemic. It is concluded that the risk factors that affect the physical and mental health of the teachers of nursing of the University of Guayaquil are related to the excess of activities that they must realize in front of a computer, the same ones that alter patterns life of each one of those involved.